THE EFFECT OF TONGUE TWISTER TOWARD STUDENTS’ PRONUNCIATION ABILITY - Fenti Dwi Luviana; Sukirno; Willy Anugrah Gumilang (LinguA-LiterA: Journal of English Language Teaching Learning and Literature, 2018)
Having a fluent and a correct pronunciation when people are speaking English is the aim of designing this research. The lack of the awareness about how the importance of teaching pronunciation during the teaching-learning process makes the researcher encourages to do the research by applying one technique that is considered to improve students' pronunciation ability, namely tongue twisters. This technique is also chosen because it is fun and interesting. This research was carried out with a pre-experimental design that consisted of three stages applied to students of SMP Global Karangan as the subject of this research. The first stage, the researcher assessed the ability of students to pronounce the words through a pre-test. The second stage, the researcher treated the students where students got the knowledge about tongue twister. The third stage, students were given a post-test to reassess the pronunciation ability and were compared with the results of the pre-test before to find out the level of difference before and after getting treatment. After getting the results, the researcher proceeded to the analysis stage which was carried out the quantitative method which was using SPSS. The results of the analysis showed that there was an effect of tongue twister toward students' pronunciation ability